2011
DOI: 10.1159/000328516
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-Activated AMPK/SIRT1/Autophagy in Cellular Models of Parkinson’s Disease

Abstract: Excessive misfolded proteins and/or dysfunctional mitochondria, which may cause energy deficiency, have been implicated in the etiopathogenesis of Parkinson’s disease (PD). Enhanced clearance of misfolded proteins or injured mitochondria via autophagy has been reported to have neuroprotective roles in PD models. The fact that resveratrol is a known compound with multiple beneficial effects similar to those associated with energy metabolism led us to explore whether neuroprotective effects of resveratrol are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
278
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(301 citation statements)
references
References 64 publications
18
278
2
3
Order By: Relevance
“…We previously reported that the treatment of porcine oocytes with resveratrol upregulates the expression of SIRT1 and induces mitochondrial biogenesis and degradation during porcine oocyte maturation (Sato et al 2014). In line with this, Wu et al (2011) reported that the treatment of SH-SY-5Y cells with resveratrol activates AMPK/SIRT1 and autophagy. CCCP treatment of mouse embryonic fibroblasts has furthermore been shown to induce AMPK activation and increase the number of LC3 dots in cells (Kwon et al 2011).…”
Section: Mitochondrial Impairments and Kineticssupporting
confidence: 55%
See 1 more Smart Citation
“…We previously reported that the treatment of porcine oocytes with resveratrol upregulates the expression of SIRT1 and induces mitochondrial biogenesis and degradation during porcine oocyte maturation (Sato et al 2014). In line with this, Wu et al (2011) reported that the treatment of SH-SY-5Y cells with resveratrol activates AMPK/SIRT1 and autophagy. CCCP treatment of mouse embryonic fibroblasts has furthermore been shown to induce AMPK activation and increase the number of LC3 dots in cells (Kwon et al 2011).…”
Section: Mitochondrial Impairments and Kineticssupporting
confidence: 55%
“…SIRT1 and AMP-activated protein kinase (AMPK) activate PGC1a by deacethylation and phosphorylation, resulting in mitochondrial biosynthesis through NRF1 and mitochondrial transcription factor A (TFAM) (Price et al 2012). In addition, SIRT1 and AMPK play a role in autophagy (Wu et al 2011) Treatment of cells with carbonyl cyanide-m-chlorophenylhydrazone (CCCP), an inhibitor of oxidative phosphorylation, induces autophagy to remove damaged mitochondria (Ding et al 2010, Lee et al 2010, Cali et al 2013. In our study, we investigated whether a mitochondrial qualitycontrol system is present in oocytes by investigating mitochondrial function, DNA copy number and expression of genes related to mitochondrial generation and oocyte parthenogenetic developmental abilities, following CCCP-induced mitochondrial dysfunction, on the premise that induced dysfunction would upregulate mitochondrial turnover during oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, potent therapeutic effects of resveratrol administration were reported in animal models of Alzheimer's disease and accelerated ageing [10,26,46], multiple sclerosis [47,48], Huntington's disease [9,49], Parkinson's disease [22,50], and even reducing peripheral axonal degeneration [51] or promoting functional recovery after traumatic spinal cord injury [23]. In this sense, resveratrol has been also reported to exert neuroprotection on in vitro models of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol administration has been shown to provide beneficial effects on several neurodegenerative disease models, such as Alzheimer's disease [10] and Parkinson's disease [22] and in traumatic [23] and ischemic injuries to the central nervous system [24]. Since previous studies showed that resveratrol administration protects MN on in vitro ALS models [25,26], the main goal of the present work was to assess the potential therapeutic effect of a resveratrol-enriched diet in the SOD1 G93A mouse model of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2014) was demonstrated to reduce SOD1 and p62/SQSTM1 aggregation, as well as ubiquitinated protein accumulation, thereby inhibiting the pro-apoptotic pathway in SOD1 G93A mice (Zhang et al, 2014). Furthermore, resveratrol and curcumin exhibit a neuroprotective activity in models of neurodegenerative disorders, working as indirect mTOR-dependent activators of autophagy (Jeong et al, 2012;Jiang et al, 2013;Wu et al, 2011).…”
Section: Autophagy As Therapeutic Targetmentioning
confidence: 99%